Beyond BMI: Muscle Mass Correlates with Reduced Low Back Pain Disability in Pre-Elderly Adults - Susi Susanti; Resti Nurpratiwi; Laksmita Dewi Adzillina; Tita Rachma Ayuningtyas; Firdausi Kahfi Maulana (Journal of Sports Medicine and Physiotherapy, 2025)
Background: Low back pain (LBP) ranks among the most common musculoskeletal disorders that impact functional mobility and overall quality of life, especially in older adults who work at school teachers. Although body mass index (BMI) is frequently utilized as an indicator of health risk, it does not differentiate between fat and muscle mass, which may have varying implications for LBP risk. Objectives: The objective of this research was to examine the correlation between body composition (BMI, muscle mass, body fat & visceral fat percentage) and the likelihood of experiencing LBP in pre-elderly individuals. Methods: This study used a cross sectional analytic design and included 72 pre-elderly participants between 45-59 years old, who were selected through purposive sampling. Body composition metrics were obtained using a bioelectrical impedance analysis device, while LBP disability was evaluated by Oswestry Disability Index (ODI) questionnaire. The data were analyzed utilizing Spearman correlation due to the non-normal distribution of the variables with the aid of IBM SPSS Statistic 26.0 software. Results: The analysis indicated a moderate negative correlation between muscle mass and ODI scores (r2 = -0.488, p = 0.001), implying that higher muscle mass correlates with reduced LBP related disability. Visceral fat percentage exhibited a weak yet significant negative correlation with ODI (r2 = -0.293, p = 0.012), whereas BMI and body fat percentage did not show significant correlation with LBP. Conclusion: Muscle mass was identified as the most critical protective factor against LBP in pre-elderly adults, while BMI and total body fat did not serve as predictors of LBP risk. These results highlight the significance of muscle preservation in strategies aimed at preventing LBP and suggest that BMI alone is inadequate for evaluating musculoskeletal health risks in aging populations. Keywords: body composition, low back pain, teacher school.